The role of Kompas.id platform as a forum for the development of newspaper literature in the digital era - Ayuningrum, Annisa Dwi; Larasati, Ade Kurnia Putri; Putri, Syaimah Kusnari; Bachtiar, Ahmad (Diksi, 2022)
The newspaper has long been an outlet for publishing written work, and through technological breakthroughs that have impacted and advanced the publishing industry, the readers benefit from online newspapers. This digital media makes possible simple and rapid access to digital information channels, including the news portal Kompas.id. The present study, library research, aims to reveal the newspaper literature that promotes an appreciation for Indonesian literature. Screenshots and attentive listening were employed as documentation strategies during the data collecting process which involve some analysis of literary content on Kompas.id. The researcher's technical analysis includes the following steps: (1) Identifying literary products pertinent to the investigation, (2) accessing the Kompas.id software, (2) registering for a user account on the Kompas.id website, (3) attentively listening to the literary works read on the Kompas.id platform, (5) examining the literary content on the platform, and (6) summarizing and presenting the findings. The results of the study demonstrated that newspaper literature relatively evolved in this digital era, making it simpler for authors to submit their works and for readers to enjoy them. The Kompas.id, site publishes literary pieces that serve to enlighten, educate, and transmit moral values to their readers, as well as stimulating their interest on reading through its up-to-date and original works of literature This likely exemplifies how the growth of digital media has influenced Indonesian literature in a beneficial way.Keywords: newspaper literature, Kompas.id, technology, digital era